2010
DOI: 10.1111/j.1463-6409.2010.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic relationships of hymenolepidid cestodes of rodents and shrews inferred from sequences of 28S ribosomal RNA

Abstract: Henttonen, H. (2010). Systematic relationships of hymenolepidid cestodes of rodents and shrews inferred from sequences of 28S ribosomal RNA. -Zoologica Scripta, 39, 631-641. This study attempts to elucidate systematic relationships of hymenolepidid cestodes of rodents (18 species), shrews (13 species) and bats (one species) using sequences of partial 28S ribosomal RNA, with special reference to the genus Rodentolepis. The main finding is the presence of four multispecies clades of hymenolepidid cestodes showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 21 publications
10
96
1
Order By: Relevance
“…Phylogeny Spassky (1992) considered hymenolepidids with an unarmed scolex parasitizing mammalian hosts to be paraphyletic. Recent molecular phylogenetic studies (Haukisalmi et al 2010a;Greiman and Tkach 2012) have corroborated this hypothesis and have demonstrated that the loss of the rostellum, or the rostellar armature, has occurred in several independent lineages of hymenolepidids among mammals. For example, this is exemplified by species of the Arostrilepis horrida complex (syn.…”
Section: Scolex Anatomy and Functionmentioning
confidence: 87%
See 3 more Smart Citations
“…Phylogeny Spassky (1992) considered hymenolepidids with an unarmed scolex parasitizing mammalian hosts to be paraphyletic. Recent molecular phylogenetic studies (Haukisalmi et al 2010a;Greiman and Tkach 2012) have corroborated this hypothesis and have demonstrated that the loss of the rostellum, or the rostellar armature, has occurred in several independent lineages of hymenolepidids among mammals. For example, this is exemplified by species of the Arostrilepis horrida complex (syn.…”
Section: Scolex Anatomy and Functionmentioning
confidence: 87%
“…Access to new comparative materials for concurrent or integrated morphological/molecular analyses is essential to enhance our ability to more completely document parasite faunal diversity among Peromyscus spp. and other rodents (e.g., Haukisalmi et al 2010a;Makarikov et al 2013a, b). Deposition of specimens from inventories is a basic foundation for characterization of faunal structure (e.g., Hoberg et al 2009) and is increasingly necessary given the expanding recognition of cryptic diversity across many groups of parasites and hosts (Pérez-Ponce de León and Nadler 2010).…”
Section: Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 43 molecular phylogenetic studies on interspecific and intergeneric relationships within 44 the family are still in their infancy [2]. Although a few members of the genus 45 Hymenolepis sensu lato are of medical importance as pathogenic organisms, their 46 taxonomy is still controversial, particularly that of Hymenolepis nana [2] …”
mentioning
confidence: 99%